The liberal state and the liberal goverment: Mod-ern aspect of society management - Kuznetsov, Mikhail A. (Opción, 2020)
The article attempts to reveal the features of functioning of the liberal state of the Russian Federation via the methodology of the sci-entist about the method of scientific cognition and transformation of society. As a result, the modern liberalism of the Russian Federation serves global financial monopolies, which is why the liberal govern-ment does everything popular for them, which results in unpopular measures for the people. In conclusion, it is necessary to discuss the provisions of the social state in the Legislative Assembly of the Rus-sian Federation and adopt a law on their implementation in the man-agement policy.